Clinical Profile of Dengue Fever and Dengue Haemorrhagic Fever in Children during an Outbreak in Timor Leste, 2005 (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 44-49 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8804